Chronic and asymptomatic diseases influence the control of hypertension treatment in primary care - Angela Maria Geraldo Pierin; Stael Silvana Bagno Eleutério da Silva; Flávia Cortez Colósimo; Gabriela de Andrade Toma; Talita de Souza Serafim; Paolo Meneghin
Abstract OBJECTIVE To identify the association between blood pressure control and the following variables: a) bio-social and lifestyle characteristics of hypertensive patients; and b) factors related to the antihypertensive treatment. METHODS This is an exploratory study with 290 people with hypertension from primary care. We used a specific instrument, self-administered, with 21 questions on factors that can hinder treatment, divided into four dimensions: medication, socioeconomic, institutional and personal beliefs. We adopted a significance level of p <0.05. RESULTS The control of blood pressure was associated (p <0.05) with female gender, Caucasian ethnicity, primary/secondary education, not drinking alcohol, higher income and regular physical activity. Regarding the factors that can hinder treatment, there was association of hypertension control with only two questions: "feel nothing" and "have to do treatment for life". CONCLUSION Sociodemographic variables and beliefs concerning the absence of symptoms and chronicity of the disease influenced the control of hypertension and should be considered in the adherence process to the treatment.